Amplifikasi Dominasi Wanita Pada Media (Studi Wacana Film Tilik) - Irwanto Irwanto Irwanto; Laurensia Retno Hariatiningsih (Universitas Bina Sarana Informatika, 2021)
AbstractFilm is a medium to convey messages to the public. There is space in the film that can be used as a means of conveying ideology. The film creators use this space as a means to amplify the ideology. Films have enormous potential in transferring ideology to the public without significant obstacles. Likewise, what is found in the film Tilik. The scenes in the film are constructed to convey a message about the domination of women in social life. This is shown in several scenes in the film. One of them was when the figure of bu Tejo arrogantly protested the decision of the police officer who ticketed the car he was in. Here is described the attitude, diction, which narrative very clearly represents the dominance of women. Besides that, there are also other scenes that depict the dominance of women in the realities of life that are told in the film. This research was conducted with a qualitative approach through the critical discourse analysis method. The research revealed that Tilik's film amplifies the values of female domination in life.Keyword: Female Domination, Film, Amplification